Improved DNA extraction technique from clot for the diagnosis of Chagas disease. - Holger Mayta; Yomara K Romero; Alejandra Pando; Manuela Verastegui; Freddy Tinajeros; Ricardo Bozo; Josephine Henderson-Frost; Rony Colanzi; Jorge Flores; Richard Lerner; Caryn Bern; Robert H Gilman; et al. (Public Library of Science (PLoS), 2019)
Background The detection of Trypanosoma cruzi genetic material in clinical samples is considered an important diagnostic tool for Chagas disease. We have previously demonstrated that PCR using clot samples yields greater sensitivity than either buffy coat or whole blood samples. However, phenol-chloroform DNA extraction from clot samples is difficult and toxic. The objective of the present study was to improve and develop a more sensitive method to recover parasite DNA from clot samples for the diagnosis of Chagas disease. Methodology/principal findings A total of 265 match pair samples of whole blood-guanidine (GEB) and clot samples were analyzed; 150 were from Chagas seropositive subjects. DNA was extracted from both whole blood-guanidine samples, using a previously standardized methodology, and from clot samples, using a newly developed methodology based on a combination of the FastPrep technique and the standard method for GEB extraction. A qPCR targeting the nuclear satellite sequences was used to compare the sample source and the extraction method. Of the 150 samples from Chagas positive individuals by serology, 47 samples tested positive by qPCR with DNA extracted by both GEB and clot, but an additional 13 samples tested positive only in DNA extracted from clot. No serology-negative samples resulted positive when tested by qPCR. Conclusions The new methodology for DNA extraction from clot samples improves the molecular diagnosis of Chagas disease.